(untitled) (International Journal of Innovative Technologies in Economy, 2024)
The article considers the role of innovation in construction. The results of a survey of representatives of the construction industry on innovative investments are presented. Theoretical aspects of digitalisation in the construction process are studied, and the passive house concepts are considered. The impact of innovation on the construction sector is analysed, as are the indicators determining the level of innovativeness of construction.